Populism, Twitter, and COVID-19: Narrative, Fantasies, and Desires - Cervi, Laura (2021)
During a global pandemic, the great impact of populist discourse on the construction of social reality is undeniable. This study analyzes the fantasmatic dimension of political discourse from Donald Trump’s and Jair Bolsonaro’s Twitter accounts between 1 March and 31 May. To do so, it applies a Clause-Based Semantic Text Analysis (CBSTA) methodology that categorizes speech in Subject-Verb-Object (SVO) triplets. The study findings show that in spite of the Coronavirus pandemic, the main beatific and horrific subjects remain the core populist signifiers: the people and the elite. While Bolsonaro’s narrative was predominantly beatific, centered on the government, Trump’s was mostly horrific, centered on the elite. Trump signified the pandemic as a subject and an enemy to be defeated, whereas Bolsonaro portrayed it as a circumstance. Finally, both leaders defined the people as working people, therefore their concerns about the pandemic were focused on the people’s ability to work.